Lipid status in transgender patients receiving hormone affirming therapy for 6 months - Jovanović, Nina; Vujović, Svetlana (Medicinski podmladak, 2024)
Introduction: The term “transgender” refers to a person whose sex assigned at birth does not match their gender identity. Tanssexualism can be diagnosed in all ages, aldo first sines can be seen in early childhood. This condition is treated with cross-sex hormone therapy (CSHT) and surgical reconstructions with the goal of maching the physical sex with the one that the person identifies with. Aim: To study effects of cross-sec hormone therapy with testosterone on anthropometric characteristics, lipid and hormone status in female to male(FtM) transgenders. Material and methods: Study includes 31 FtM patients with gender identity disorder. Beginning of CSHT was at age 26.03 ± 5.21. Patients were treated on Clinic of endocrinology, diabetes and disease of metabolism, Clinical center of Serbia. Lipid and hormone status before and during therapy were analyzed. Results: BMI has increased significantly. Mean levels of HDL and Lp(a) were increased significantly, and there were a significant decrease in ApoA1. There were no changes in other lipid levels. During six months of testosterone therapy levels of FSH, LH and estradiol showed a significant decrease, while testosterone has increased significantly. We found higher values of RBC and hemoglobin. Conclusion: CSHT do not lead to pathological alteration of lipid profile if dosed properly.